Is Mexico beyond mestizaje? Blackness, race mixture, and discrimination. Issue 1 (2nd January 2023) - Sue, Christina A.
ABSTRACT: In the 1980s and 1990s, a wave of multiculturalism swept across Latin America, following long-standing ideologies of mestizaje which glorified the region's biological and cultural mixture and asserted that such mixture precluded the existence of racism. A decade or so later, countries in the region enacted another set of reforms focused on combatting ethnoracial discrimination and inequality. Whereas many view these changes as indicating the downfall of mestizaje ideologies, others argue that they may not be as distinct from mestizaje as it may appear. I reflect on this question in the context of Mexico, drawing on data from recent government and private surveys to assess the current state of Mexican national ideology, both at the national level and in a local site of blackness. I provide novel findings about the kinds and prevalence of various forms of black identification, the extent of black-indigenous boundary crossing, and the strength of attitudes about mestizaje and racism. Ultimately, I show how ideologies and discourses associated with mestizaje, multiculturalism, and racial equality are absorbed at the popular level in ways that suggest that at least some parts of the ideology of mestizaje are enduring or evolving to accommodate these new ethnoracial projects.